Potassium nutrition of abaca and a survey of the available potassium of an abaca plantation in Costa Rica - Díaz-Romeu, Roberto (IICA, Turrialba (Costa Rica), 2014)
Tesis (Mag.Agr.) - IICA, Turrialba (Costa Rica), 1955